Simulation Study on Stress Analysis of Pipe Supported Round Bar PEEK due to Heavy Load - Azhari, Nurul Nabilah (IRC, 2018)

(untitled)
The purpose of this report is to develop a pipe stress analysis when affected by load weight using simulation study. Pipe stress analysis is necessary to indicate whether the pipe arrangement in the pipe operation can cope with weight, pressure stress and thermal at safe operation levels. Besides, the pipe stress analysis also functions in ensuring that the piping is well supported and does not deflect or fall under its own weight. Pipe support components, piping engineering in process industry and piping stress analysis due to load cases were studied in the theory section of this report. Pipe support is one of the main factors that affect the performance of piping operation. To prevent from over stress between the pipe and pipe support, the suitable pipe size with appropriate load needs to be place on the specific pipe support. By utilizing the theory in literature review and help from the experience employee, a new way of determining the stress analysis of pipe and the best pipe support to prevent corrosion was developed and identified. A semi-cylinder rod is place between pipe and supporting structure to prevent corrosion. The stress analysis of pipe is usually done by using the finite element method (FEM). The use of simulation study using FEM, ANSYS software can help for a better result in analyse the pipe stress analysis. The theoretical analysis by manual calculation will help to support the result of the simulation. As a result, the appropriate pipe size to be support on specific pipe support can be identify. Lastly, the summary from the research conducted was stated and future work was listed for further study which follow from the result obtained.